Water Swollen Natural Rubber - KHONGTONG, Sureurg; FUNGCHONLAJIT, Narong (Walailak Journal of Science and Technology (WJST), 2011)
Modification of natural rubber by grafting of maleic anhydride yielded a water absorbable substrate. It was found that water contact angles of treated samples declined as the concentrations of maleic anhydride increased reflecting higher water compatibility in grafted samples. Submergence in water of these samples caused dramatic swelling with the water content up to about 60 wt %.